Proteomic Comparison of the Cytotoxicology of Two Diastereomers of Citreamicin Reveals Differentially Activation of NF-κB Pathway - Liu, Ling-Li; Sun, Jin; Xu, Ying; He, Li-Sheng; Kondethimmanahalli, Chandramouli; Qian, Pei-Yuan (Frontiers in Marine Science, 2020)
Citreamicin ε is a group of antitumor compounds produced by Streptomyces species. Cytotoxicology study of two diastereomers, citreamicin ε A and B, showed different apoptotic effects on PtK2 cells with IC50 values of 0.086 μM and 0.025 μM, respectively. Thus, we performed an iTRAQ based quantitative proteomic analysis in order to reveal the mechanism of cytotoxicity of citreamicin ε A and B in PtK2 cells. A total of 1079 proteins were identified and quantified, among which 103 and 94 proteins displayed significantly changes in expression levels after the treatment of citreamicin ε A and B, respectively. These significantly differentially expressed proteins (DEPs) were further annotated by GO, KEGG, and protein-protein interaction analysis, which revealed the involvement of eight molecular pathways. Among them, expression trends of proteins involved in the NF-κB pathway displayed the opposite between the two diastereomer treatments, indicating different modes of action of these two compounds. Citreamicin ε A treatment induced rapid activation of the NF-κB pathway, which might promote cell survival and resulted in lower toxicity. Our comparative proteomic analysis provided molecular evidence on the toxicity of two diastereomers compounds to cells, which may shed new lights on future mechanism study of these antitumor compounds.